Reconceptualising authenticity for English as a global language - Pinner, Richard S. (Bristol :Multilingual Matters, 2016)
This book explores authenticity as it relates to second language acquisition with a focus on the instruction of English as a foreign language. It discusses the theoretical issues surrounding authenticity and presents it as a complex dynamic construct that can only be understood by examining it from social, individual and contextual dimensions.
1. Introduction to the book -- 2. Existential, philosophical and theoretical underpinnings -- 3. English as a global language. -- 4. Authenticity in language teaching -- 5. The Authenticity continuum -- 6. Authenticity in bilingual educational contexts. -- 7. New media as a catalyst for authenticity -- 8. Conclusion -- 9. References.
Includes bibliographical references (pages 170-187) and index.
Keywords: English language -- Globalization; English language -- Study and teaching -- Foreign speakers